Assessment of Thyroid Function and Cortisol Levels in Iraqi Patients with Vitiligo - Mohsin, Fatima H.; Hussein, Talib A.; Abdulqahar , Ghassan H. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: The loss of functioning melanocytes in the skin causes vitiligo, an acquired autoimmune condition that manifests as big, white, unsightly patches on the skin. Melanocyte loss is caused by several reasons, including oxidative stress, inflammation, autoimmune, and metabolic problems, while the exact etiopathology of the condition remains unknown. There is a relationship between vitiligo, thyroid hormones, and cortisol levels.Objective: The study aims to measure cortisol hormone levels in the serum of vitiligo patients and examine the thyroid hormones (T3, T4, and TSH).Methods: In this case-control study, 80 vitiligo patients diagnosed between November 2023 and February 2024 by dermatologists at the Dermatology and Venereology Center in Medical City, Baghdad, were included. The control group consisted of 40 healthy people. Everyone had a venous blood sample. Cortisol levels and thyroid hormones were assessed using the electrochemiluminescence immunoassay method.Results: The control group's mean age was 29.5 ± 13.28, whereas the patient group was 28.9 ± 14.15. There were no statistically significant differences in age between study groups.  Age and gender differences were not considered between the two groups. The patient group had significantly higher mean T3, TSH, and cortisol levels than the control group. The two groups did not differ significantly regarding T4 (P>0.05).Conclusion: A comparison of T3, TSH, and Cortisol levels revealed a difference between the two groups, but no difference in T4 levels was observed. More extensive research with larger sample sizes is required to clarify these findings. levels showed up. More extensive research with larger sample sizes is required to clarify these findings.